PENGGUNAAN LEMBAR KEGIATAN SISWA UNTUK MENGEMBANGKAN PEMAHAMAN KONSEP PEMBELAJARAN IPS : PTK di Kelas VIII A SMP Laboratorium Percontohan Universitas Pendidikan Indonesia - Meisendi, Dena Yemin (2013)
This study originated from the writer's concern towards an issue occurred in eight graders A of Laboratory Junior High School of Indonesia University of Education related to understanding concepts of social studies learning. The issue is finding from conducted observation in several meetings of April to June 2013. Indicator of the problems which is encountered is low interest in reading, less focus or concentration of learners in learning process, less understanding of the meaning of social studies, low participation of learners in learning, unwell paradigm of social studies, lack of initiative participation in learning process, and low learning results. Reviewing the examined issues relate to the learning process, the researcher chose Classroom Action Research (CAR) with 5 cycles of Kemmis and Mc. Taggart research design. Alternative selected solutions, namely Student Activity Sheet. Implementation of worksheets learning activities as an alternative in purpose to develope the social studies concepts understanding can be categorized in good level. The development of understanding of social sciences concepts can be seen from the development of understanding of learning indicators of social studies concepts such as able to explain the concepts and studied materials, able to interpret the understanding, able to apply owned knowledge, have perspective, empathized, and have self-knowledge. All aspects have evolved from low quality of the first cycle till the fifth ones, medium, and good quality with 49,1%, 62,9%, 73,1%, 85,2%, and 85,2% percentages in 5th cycle. In conclusion, the use of worksheets can develop the understanding of social studies concepts. Keywords: Student Activity Sheet, Understanding Social Studies Learning Concept